Contemporary British autoethnography - Short, Nigel P.; Turner, Lydia; Grant, Alec (Rotterdam, The Netherlands : Sense Publishers, 2013)
This engaging, informative book makes an exciting contribution to current discussions about the challenges and uses of contemporary autoethnography. Authors from a range of disciplines 'show and tell' us how they have created autoethnographies, demonstrating a rich blend of theories, ethical research practices, and performances of identities and voice, linking all of those with the socio-cultural forces that impact and shape the person. The book will be a useful resource for new and experienced researchers; academics who teach and supervise post-graduate students; and practitioners in social science who are seeking meaningful ways to conduct research. This should be required reading for all qualitative research training.
Introduction / Alec Grant, Nigel P. Short and Lydia Turner -- When we got to the top of elm grove / Mike Hayler -- Writing teaching and survival in mental health / Alec Grant -- Cultural constraints / David Carless -- Leaving the blood in / Jess Moriarty -- A truth waiting for a telling / Kitrina Douglas -- An englishman abroad / Nigel P. Short -- Ash Wednesdays / Jonathan Wyatt -- Assemblage/ethnography / Ken Gale and Jonathan Wyatt -- Writing forms of fiction / David Gilbourne and Phillip Marshall -- Didn't you used to be ...? / Nigel P. Short -- Artificial Persons and the Academy / Brett Smith -- Autoethnography at the will of the body / Andrew C. Sparkes -- The Evocative autoethnographic I / Lydia Turner -- Coda / Lydia Turner, Nigel P. Short and Alec Grant.
Includes bibliographical references.
Print version record.
Added to collection customer.56279.3
Keywords: Autobiography -- English authors; Ethnology -- Great Britain; Ethnologie -- Grande-Bretagne.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; BIOGRAPHY & AUTOBIOGRAPHY -- Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY -- Political; BIOGRAPHY & AUTOBIOGRAPHY -- Presidents & Heads of State; BIOGRAPHY & AUTOBIOGRAPHY -- Reference; BIOGRAPHY & AUTOBIOGRAPHY -- Rich & Famous; BIOGRAPHY & AUTOBIOGRAPHY -- Royalty; Droit; Sciences sociales; Sciences humaines; Autobiography -- English authors; Ethnology; Great Britain